Implementation Of Biology Learning At Xaverius Senior High School Lubuklinggau - Wulandari Wulandari; Sri Wardhani; Indawan Indawan (Universitas Muhammadiyah Prof. Dr. Hamka, 2021)
Background: Online learning changes the learning pattern that is usually done face-to-face into a distance education system, so there will be factors that influence it. This also has an impact on biology lessons at Xaverius High School Lubuklinggau. This study aims to determine the perception of the implementation of online learning in biology lessons and determine the factors that influence it. Methods: this research uses descriptive qualitative with data collection techniques using observation, interviews, questionnaires, and documentation which are then analyzed by technical analysis of Miles & Huberman. The research subjects were biology teachers and all students of grades X, XI, and XII science at Xaverius High School Lubuklinggau. Results: the implementation of learning in biology lessons that have been carried out at Xaverius Lubuklinggau High School there are planning, implementation and evaluation activities as well as face-to-face learning, but in the implementation there are factors that influence, namely the material cannot be explained, the response of class X students is less active, supervision of the assessment, the ability of teachers to use various educational applications, difficulty in assessing the character of students, some students do not understand the material provided, and the learning environment. Conclusion. The implementation of online learning that is applied there are still planning, implementation and evaluation activities, but in the implementation there are several factors that influence both supporting and inhibiting factors.